"Nature, environment and society: conservation, governance and transformation in India / edited by Nicolas Laine and T.B. Subba" - "Laine, Nicolas (ed.);Subba, T. B. (ed.)" (Hyderabad, 2012)
This book well represent a broad span of core themes in human nature conflicts in India, from the effects on local societies of conservation of policies and contrasting notions of the ultimate usage of natural resources, to policy research covering thirty years of modern Indian developments.....While the individual studies centre on crucial environmental problems in India
Keywords: Environment-Social aspects